Pesquisa de sujidades, microbiana e parasitária do caldo de cana comercializado em Município do Semiárido do Rio Grande do Norte - Nunes, Sara Caroline Dantas (Universidade Federal Rural do Semi-Árido, 2021)
The diagnosis of dirt, parasites and microorganisms in sugarcane juice sold in the municipality of Mossoró, Rio Grande do Norte, was performed. Five broth guards were collected from 100% (5/5) of the available commercial technicians, packed in isothermal boxes and transported to the laboratories. The soil analysis was carried out with thorough inspection, the parasitic diagnosis looked for the presence of Trypanosoma cruzi and the microbiological analysis looked for total coliforms, Escherichia coli, Salmonella, molds and yeasts. As a result, it was possible to observe the presence of dirt in 100% (5/5) of the samples studied, with insect parts in 100% (5/5), sand 20% (1/5), plastic 20% (1/5) and hairs by 40% (2/5). However, 100% (5/5) of the samples were negative for T. cruzi, E. coli and Salmonella. In the count of total coliforms, it was observed that in 80% (4/5) of the samples there was contamination >2.50x105 CFU/mL, and 20% (1/5) the contamination was 6.7x10 CFU/mL in the second dilution and 5.3x10 CFU/ml in the third dilution. While in the research of molds and yeasts in 100% (5/5) there was contamination >1.50x105 CFU/mL. It is concluded that the juice analyzed presented a need for stricter sanitary control in the production process
Keywords: Doença de chagas (ou tripanossoma); Coliformes; Caldo de cana; Contaminação alimentar; Chagas disease (or trypanosomiasis); Coliforms; Sugarcane juice; Food contamination; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA